The cost-effectiveness of a web-based multimodal therapy for unilateral cerebral palsy: The Mitii randomized controlled trial - Comans, T.; Mihala, G.; Sakzewski, L.; Boyd, Roslyn; Scuffham, P. (Wiley-Blackwell Publishing Ltd., 2017)
Aim: To estimate the cost-effectiveness of the Mitii training system for improvements in upper limb function for children with unilateral cerebral palsy (CP). Mitii is a web-based programme delivered at home with set-up and monitoring by therapists. Method: A randomized controlled trial was conducted comparing the Mitii training programme to usual care. The Assessment of Motor and Process Skills (AMPS) and Canadian Occupational Performance Measure (COPM) were collected for each child at baseline and 20 weeks. Responders to training were characterized as those who met a minimally important difference on either the AMPS (0.3 logits) or COPM (2 points). Costs of the intervention were calculated by quantifying the equipment and staff cost. A cost per responder was calculated for each of the outcome measures. Results: A total of 102 participants (52 males, 50 females) were included in the analysis. There were significantly more responders in the training group on both the AMPS motor and process scales and the COPM performance and satisfaction scales. The cost per responder for the Mitii programme ranged from AU$3078 to AU$4191 depending on the scale used. Interpretation: The cost of delivering the Mitii training system is modest relative to the improvements in function.